Analysis of MSDs Injuries in Loading and Unloading Activities Using the Rapid Entire Body Assessment (REBA) Method - Nurul Hakim, Wafa; Zalfaa, Alyani; Efendi, Ma'aruf; Naufaldi, Raihan; Arief Firmansyah, Ridho (Jurnal Ilmiah Manajemen Kesatuan, 2024)
PT. XYZ is a company that has a port in the field of loading and unloading goods and containers with wood commodity materials, basic necessities, grocery goods and building materials. PT.XYZ experienced problem related to loading and unloading activities for transporting commodity materials which were still carried out manually and involved transporting approximately 300 ton in 1 day. Workers complain of pain in certain parts of the body, giving rise to complain of musculoskeletal disorders (MSDs) due to unergonomic work postures. The method in this research uses the Nordic body map and rapid entire body assessment (REBA) questionnaires which are useful as problem solving steps by describing several odd work postures in porters and also a classification of action that need to be taken. From the calculation result, workers need heavy equipment or facilities for loading and unloading activities, this proposal can reduce work accidents which are influenced by unsafe action and unsafe condition as well as developing productivity, efficiency and effectiveness of loading and unloading at one of docks PT.XYZ.